Edukasi Sistem Manajemen Mutu bagi Pelaku Usaha Olahan Kelapa di Sentra Pengolahan Kelapa Kabupaten Lombok Utara - AP, Yuhendra; Mi’raj Fuadi; Nur Afni; Agriananta Fahmi Hidayat; Reza Kusuma Nurrohman; Guyup Mahardhian Dwi Putra; Wiwin Apriyanditra; Surya Abdul Muttalib; M. Azhar Mustafid; Elya Antariksana Bachmida; Amuddin; Wahyudi Zulfikar (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community engagement activity was conducted on June 10, 2025, at the Coconut Processing Center in North Lombok Regency, aiming to enhance the awareness and understanding of small and medium-scale coconut-based agro-industrial actors regarding the implementation of quality management systems (QMS). The absence of standardized procedures and inadequate attention to food safety practices have contributed to the inconsistency and limited competitiveness of local processed coconut products such as virgin coconut oil (VCO), coconut milk, and other derivatives. Through the structured delivery of theoretical materials—encompassing foundational concepts of quality assurance, hygiene and sanitation principles, and the legal framework of food safety regulations—participants were introduced to the significance of quality systems in achieving product standardization and compliance. The discussion also highlighted the relevance of the Home Industry Food Permit (PIRT) as a prerequisite for legal distribution and formal market entry. The outcome of the session revealed a substantial improvement in participants’ comprehension of quality-related principles and their willingness to gradually integrate them into operational practices. This initiative demonstrates the pivotal role of universities in strengthening rural-based agribusinesses through knowledge transfer and institutional support.